(untitled) (Portuguese Journal of Family Medicine and General Practice, 2003)
Introduction: Upper respiratory tract infections (URTI) are a common reason for encounter in general practice, in spite of being usually manageable through self-care. Objective: To assess the relationship between knowledge about URTIs and frequency of use of health services by the population of Matosinhos. Study type: Quantitative, cross-sectional, analytic study. Setting: Horizonte Family Health Unit, Matosinhos Health Center. Population: Patients 18 or older from the Matosinhos area. Methods: A random sample of 288 families registered at the Matosinhos Health Center was taken. A telephone questionnaire was performed. The questionnaire included questions about demographical variables, symptoms and attitudes regarding the last URTI episode and a knowledge assessment scale. Results: Response rate was 83.7%. Attitudes at the last URTI episode were: self-care - 68%; consultation with a doctor - 25%, and none - 7%. More frequent self-care attitudes were non-pharmacological and the most looked-for doctor was own GP. Knowledge about URTIs was mostly low (61%). A statistically significant association between preferred use of health services and low knowledge level was found. Conclusion - Self-care is the first option in Matosinhos for URTI. Those seeking the health services more seem to possess the least knowledge about this health problem. Patient information about the URTIs may promote rational behaviour of its management.